2005
DOI: 10.1111/j.1365-2257.2005.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing yield of plateletpheresis using intermittent flow cell separator

Abstract: Platelet recovery in the recipient is influenced by the transfused dose of platelets, which in turn is dependent on the quality of single donor platelets (SDPs) in terms of platelet yield. Various donor factors such as predonation platelet count and Hemoglobin (Hb) concentration affect the platelet yield. A total of 61 plateletpheresis procedures performed on intermittent flow cell separator (MCS3p, Hemonetics) were evaluated for platelet yield. A relationship between predonation platelet count and Hb concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 14 publications
2
25
1
Order By: Relevance
“…In and around our region, the platelet count observed in healthy donors varies between 150 and 200 3 10 9 /L [3]. A large number of willing donors were deferred falling just short of the acceptance criteria for hemoglobin !12.5 g/dL and platelet count of !150 3 10 9 /L [4] even after repeated testing.…”
Section: Introductionmentioning
confidence: 97%
“…In and around our region, the platelet count observed in healthy donors varies between 150 and 200 3 10 9 /L [3]. A large number of willing donors were deferred falling just short of the acceptance criteria for hemoglobin !12.5 g/dL and platelet count of !150 3 10 9 /L [4] even after repeated testing.…”
Section: Introductionmentioning
confidence: 97%
“…1 The increase in medical and surgical indications for platelet transfusion along with the new technologies available, promoted and increased the use of plateletpheresis. 2 Plateletpheresis should be performed in a specific area and under the guidance and supervision of a physician. 3 Apheresis procedures are usually well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…In 12% of the procedures, the mean yield was < 3 x 10 11 /unit when the pre-donation platelet count was < 200 x 10 3 /µl 4 . Many other studies have also demonstrated significant positive correlation between the donor platelet count and the yield of the product [10][11][12] .…”
Section: Discussionmentioning
confidence: 83%